Combined Silymarin and Cotrimoxazole Therapy Attenuates Pulmonary Fibrosis in Experimental Paracoccidioidomycosis - Resende, Victor Quinholes [UNESP]; Reis-Goes, Karoline Hagata [UNESP]; Finato, Angela Carolina [UNESP]; de Fátima Almeida-Donanzam, Débora; dos Santos, Amanda Ribeiro; Perico, Jonatas [UNESP]; Amorim, Barbara Casella; Venturini, James (MDPI, 2022)
Paracoccidioidomycosis (PCM), which mainly affects rural workers, is a systemic mycosis caused by the Paracoccidioides genus that induces pulmonary sequelae in most adult patients, causing serious disability and impairing their quality of life. Silymarin is herbal medicine with an effective antifibrotic activity. Considering that in PCM, antifibrotic treatment is still not available in pulmonary fibrosis, we aimed to evaluate combined silymarin and cotrimoxazole (CMX) therapy via the intratracheal route in BALB/c mice infected with P. brasiliensis yeast. After 12 weeks of treatment, the lungs were collected for the determination of fungal burden, production of OH-proline, deposition of collagen fibers, pulmonary concentrations of cytokines, and expression of fibronectin, α-SMA, MMP-2, MMP-9, and TIMP-2. Spleen cell cultures were also performed. Our results showed that infected mice treated with combined silymarin/CMX showed lower deposition of collagen fibers in the lungs and lower pulmonary concentrations of hydroxyproline than the placebo groups. Decreased levels of TGF-β1 and fibronectin and high levels of MMP-2 and IFN-γ were also observed in this group of mice. Collectively, our findings indicate that the combination of antifungal treatment with silymarin has a potent antifibrotic effect associated with an immunomodulatory effect that potentializes the antifungal immune response.
Keywords: cotrimoxazole; paracoccidioidomycosis; pulmonary fibrosis; pulmonary sequelae; silymarin